Achievements in diagnostics and treatment of the patients with mieloid leucosis in Russian Federation - G. A. Turkina; O. Yu. Vinogradova; N. D. Khoroshko; A. I. Vorob’yov (Бюллетень сибирской медицины, 2008)
.